Education and Efficient Redistribution - Robert A.J. Dur; Coen N. Teulings (Tinbergen Institute, 2001)
Should education be subsidized for the purpose ofredistribution? The usual argument against subsidies to education abovethe primary level is that the rich take up most education, soa subsidy would increase inequality. We show that there is acounteracting effect: an increase in the stock of human capitalreduces the return to human capital and, therefore, pre-tax income inequality decreases.We consider a Walrasian world withperfect capital and insurance markets. Hence, in the absence ofa strive for redistribution, the market generates the efficient levelof investment in human capital. When there is a demand forredistribution, the general equilibrium effects on relative wagesmight make a subsidy to education an ingredient of a second-bestoptimal redistribution policy. Stimulating human capitalformation results in a compression of the wage distribution, and hencereduces the need for distortionary redistributive taxation. Wealso study the political viability of education subsidies.
Keywords: 330; Bildungspolitik; Einkommensumverteilung; Bildungsinvestition; Bildungsfinanzierung; Bildungsökonomik; Bildungsertrag; Bildungsertrag; Einkommensverteilung; Allgemeines Gleichgewicht; Theorie